Human resource management revolution in the era of digital transformation - Sami’un Sami’un; Ahmad Fatoni Karim Amirullah; I Ketut Kusuma Wijaya (Law and Economics, 2026)
This study aims to analyse the dynamics of the transformation of the role of human resources in modern organisations and to identify the key factors influencing the successful implementation of digital transformation from technological, human, and organisational perspectives. A qualitative approach was employed, utilising library research drawn from various scientific journals, academic books, and relevant publications from 2021 to 2025. Data analysis was conducted through the stages of data reduction, presentation, and drawing conclusions using thematic analysis techniques synthesised from various theoretical perspectives, such as strategic human resource management, human capital theory, and digital transformation. The findings indicate that digitalisation has transformed the role of HR into that of a strategic partner involved in data-driven decision-making processes. The implementation of technologies such as artificial intelligence, big data, and HRIS has proven capable of enhancing the effectiveness and efficiency of HR management, although it has also presented challenges in the form of a digital skills gap, resistance to change, and the risk of a diminished humanistic approach within organisations. Further findings indicate that an adaptive organisational culture and transformational leadership play a crucial role in supporting the success of digital transformation. The study’s conclusions emphasise that the success of HR transformation in the digital age is highly dependent on the synergy between technology, human resource readiness, and integrated, sustainable organisational strategies.